Effects of IL-1β and TNF-α on the Expression of P311 in Vascular Endothelial Cells and Wound Healing in Mice - Zhou, Daijun; Liu, Tengfei; Wang, Song; He, Weifeng; Qian, Wei; Luo, Gaoxing (Frontiers in Physiology, 2020)
Objective This study aimed to define the role of interleukine-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the expression of P311 in vascular endothelial cells (VECs) and in wound healing. Methods DAPI staining, a CCK-8 assay, cell migration assay, and an angiogenesis assay were used to assess the effects exerted by TNF-α and IL-1β at various concentrations on morphology, proliferation, migration, and angiogenesis of VECs. Western blot (WB) and reverse transcription-polymerase chain reaction (RT-PCR) models were employed to observe the effects exerted by proteins related to the nuclear factor-kappa B (NF-κB) signaling pathway and P311 mRNA expression. Bioinformatics analysis was performed on the binding sites of P311 and NF-κB. Finally, to investigate the effects of IL-1β and TNF-α on wound healing and the length of new epithelium in mice, we established a full-thickness wound defect model in mice. Immunohistochemistry was used to measure changes in P311, proliferating cell nuclear antigen (PCNA), vascular endothelial growth factor (VEGF), CD31 (platelet endothelial cell adhesion molecule-1, PECAM-1/CD31), as well as other related proteins. Results When levels of TNF-α and IL-1β were both 20 ng/ml, their effects on cell proliferation, cytoskeleton protein expression, cell migration, and angiogenesis were the greatest (P < 0.05). IL-1β and TNF-α at moderate concentrations effectively promoted P311 mRNA and p-NF-κB protein expression (P < 0.05), while p-NF-K b protein expression was decreased (P < 0.05). Luciferase assays showed that P311 expression was also relatively greater when stimulated at moderate concentrations (P < 0.05), while relative expression was significantly lower when the p-NF-K b inhibitor CAPE was added (P < 0.05). On 7-day wound healing rate comparison, the control, IL-1β, IL-1βab, TNF-α, and TNF-αab groups were 18, 37, 35, 39, and 36%, respectively, while control group + P311 siRNA was 31% (P < 0.05). New epithelial length, granulation tissue thickness, and number of blood vessels trends were also the same. In the control group, P311 showed lower relative expression levels than the others (P < 0.05). P311 relative expression levels trended as follows: control group > IL-1βab > IL-1β > TNF-αab > TNF-α (P < 0.05). Conclusion When IL-1β and TNF-α concentrations are moderate, they effectively promote the proliferation, expression, migration, and angiogenesis of VECs, possibly by promoting the expression of the NF-K b pathway and thereby promoting the expression of P311. In vitro experiments on mice suggest that P311 effectively promotes wound healing, and its mechanism may be closely related to PCNA, CD31, and VEGF.